2022
DOI: 10.3390/ijms23052714
|View full text |Cite
|
Sign up to set email alerts
|

Neural Crest-Derived Stem Cells (NCSCs) Obtained from Dental-Related Stem Cells (DRSCs): A Literature Review on Current Knowledge and Directions toward Translational Applications

Abstract: Evidence from dental-related stem cells (DRSCs) suggests an enhanced potential for ectodermal lineage differentiation due to their neural crest origin. Growing evidence that DRSC cultures can produce cells with a neural crest-derived stem cell (NCSC)-like phenotype supports their potential for future therapeutic approaches for neurodegenerative diseases and nerve injuries. However, most of the evidence is limited to the characterization of DRSCs as NCSCs by detecting the expression of neural crest markers. Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Indeed, studies are limited to the characterization of oral DMSCs as NCSCs by expression of neural crest markers (NCSCs) instead of testing their functional behavior. Only a few studies have observed glial differentiation enhanced or applicable in in vivo studies [ 72 ]. A systematic revision showed the importance of obtaining stability during the DMSC transplantation procedure based on control, quality, and efficacy of the cell populations, which can only be guaranteed by tackling heterogeneity even within the subgroup of stem cells isolated from human teeth that show significant differences in so far as their cell properties, such as proliferation and differentiation, in regenerative medicine [ 36 ].…”
Section: Research On Tooth Regeneration and Its Structures: Basic Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies are limited to the characterization of oral DMSCs as NCSCs by expression of neural crest markers (NCSCs) instead of testing their functional behavior. Only a few studies have observed glial differentiation enhanced or applicable in in vivo studies [ 72 ]. A systematic revision showed the importance of obtaining stability during the DMSC transplantation procedure based on control, quality, and efficacy of the cell populations, which can only be guaranteed by tackling heterogeneity even within the subgroup of stem cells isolated from human teeth that show significant differences in so far as their cell properties, such as proliferation and differentiation, in regenerative medicine [ 36 ].…”
Section: Research On Tooth Regeneration and Its Structures: Basic Con...mentioning
confidence: 99%
“…In addition, safety concerns are included due to the potential teratogenic or neoplastic risk and the transmission of infectious diseases, among other no less important complications [ 85 , 88 ]. Also, a current problem is that several of the existing protocols do not meet manufacturing standards for transferability to a clinical setting [ 72 ]. In any case, a recent systematic study reflects the effectiveness of oral clinical studies with complete results on DMSC-mediated therapies compared to current methods based on patient evidence and concludes with the efficacy of the use of these cells in various pathologies.…”
Section: Translational Applications Of Msc From the Oral Cavitymentioning
confidence: 99%